2011
DOI: 10.1093/europace/eur069
|View full text |Cite
|
Sign up to set email alerts
|

Amnesia for loss of consciousness is common in vasovagal syncope

Abstract: Amnesia for loss of consciousness is common in VVS. Although more prevalent, it is not unique to older age-groups. Absence of syncope associated bradycardia during HUT testing predicts for A-LOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 23 publications
2
70
0
2
Order By: Relevance
“…35,45,[666][667][668][669][670][671][672][673][674][675] The vulnerability of older adults to syncope increases because of age-associated cardiovascular and autonomic changes, decreased fluid conservation, 45,671,[676][677][678] and an increased probability of developing multiple concurrent morbidities (with their associated pharmacological treatments) that can overwhelm homeostasis. In many instances, a syncopal event in an older adult is multifactorial, with many predisposing factors present simultaneously.…”
Section: Geriatric Patients: Recommendationsmentioning
confidence: 99%
“…35,45,[666][667][668][669][670][671][672][673][674][675] The vulnerability of older adults to syncope increases because of age-associated cardiovascular and autonomic changes, decreased fluid conservation, 45,671,[676][677][678] and an increased probability of developing multiple concurrent morbidities (with their associated pharmacological treatments) that can overwhelm homeostasis. In many instances, a syncopal event in an older adult is multifactorial, with many predisposing factors present simultaneously.…”
Section: Geriatric Patients: Recommendationsmentioning
confidence: 99%
“…Unexplained falls are also common in the elderly [19]. The symptoms of arterial hypotension may be vague, and prodromal symptoms may last for only a short time or even be absent [20,21]. Neurocardiogenic reflex may also provoke a sudden loss of consciousness, especially due to atrioventricular block or, in less common cases, junctional escape rhythm [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have recently demonstrated that almost 50% of patients during head up tilt test, whatever their age but predominantly older patients, denied any TLOC, although the loss of consciousness was confirmed by nurses and/or doctors. 6 In patients in whom TLOC remains uncertain, occurrence of loss of postural tone is a strong argument to consider that TLOC has really occurred.…”
Section: Transient Loss Of Consciousnessmentioning
confidence: 99%